Pengaruh Metode Debat Aktif terhadap Hasil Belajar Tematik Peserta Didik Kelas V Sekolah Dasar - Destini, Frida; Astuti, Nelly; Merlinda, Irma (Didaktika, 2022)
The problem of this research was the low thematic learning outcomes of fifth-grade students caused by the lack of use of a suitable learning method. The purpose of this study was to determine the effect of the active debate method on the learning outcomes of fifth-grade elementary school students. The research method used is quasi-experimental and the data used is quantitative. The research design used is a non-equivalent control group design. The population in this study were all fifth-grade students of State Elementary School of 1 Rajabasa Bandar Lampung, totaling 35 students. The sampling technique used was the saturated sampling technique. Data collection using test sheets and documentation. The results of the data analysis technique using the t-test formula showed that there was an effect of the active debate method on the learning outcomes of fifth-grade elementary school students percentage of 79%. The increase in learning outcomes is due to the suitability of the material with the debate issues discussed daily so that students feel interested and it is hoped that it can be used as an alternative to the use of learning methods to improve students’ thematic learning outcomes.